INTIMIDASI, KEKERASAN DAN PELECEHAN TERHADAP PEREMPUAN MINANGKABAU DALAM CERPEN SANG GURU JUKI KARYA A.A NAVIS : STUDI HISTORIOGRAFI - Rima Yulsyaf Febri; Etmi Hardi (Jurnal Kronologi, 2022)
This study discusses the description of Minangkabau women during PRRI in the short story Sang Guru Juki by A.A Navis. There are many scientific works that examine the PRRI period in Central Sumatra, but very few discuss women at that time. Intimidation, sexual violence and harassment have a negative impact on women's lives. These actions make women feel ashamed, humiliated, afraid and traumatized. During the upheaval, women are in a dangerous position, they are weak, have no weapons and need to be protected. Women who are usually respected have shifted into women who have lost their identity. The purpose of this research; describes Minangkabau women during the PRRI upheaval in the short story Sang Guru Juki by A.A Navis. This research is a historical research with library research method without going directly to the field. Literary works can be used as a source of support in historical research, which escapes the eyes of historians. The results of this study: the description of Minangkabau women in the short story Sang Guru Juki, placing women in a disadvantaged position, fear, anxiety and trauma are still felt by women today, especially when considering the treatment of APRI and PRRI individuals.